Comparative Analysis of Impairment Loss Allowance Before and After the Implementation of SAK EP and Its Effect on Profit at PT. BPR Duta Paramarta - Erna Susilawaty Sebayang; Hamonangan Justinus Gultom (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to compare the allowance for impairment losses before and after the implementation of Indonesian Financial Accounting Standards for Private Entities (SAK EP) and to examine its impact on the profitability of PT BPR Duta Paramarta. Using a quantitative and comparative approach with secondary financial data, the analysis employed descriptive statistics and an independent sample t-test to assess differences in impairment provisions under SAK ETAP and SAK EP. The results reveal a significant difference in the calculation of impairment loss allowance between the two standards, confirming the shift from a rule-based to a principle-based approach in credit risk assessment. However, regression analysis indicates that impairment loss allowance under SAK EP has a positive but not statistically significant effect on profit. These findings suggest that while the adoption of SAK EP leads to more comprehensive recognition of credit risk, its immediate impact on profitability is limited. The study contributes to the understanding of regulatory changes in financial reporting and their implications for the banking sector, particularly rural banks. Keywords: financial reporting, incurred loss concept, credit risk management, profitability, regulatory compliance.